2013
DOI: 10.1002/nur.21535
|View full text |Cite
|
Sign up to set email alerts
|

Individual, family, social, and cultural predictors of depressed mood in former soviet immigrant couples

Abstract: Gender differences in predictors of depression for married couples from the former Soviet Union were examined in a cross-sectional, descriptive analysis. Data were collected during a longitudinal study of post-migration health and adaptation. The sample included 308 men and women (154 couples), ages 40-79, who had lived in the US for an average of 6 years. Generativity, marital satisfaction and communication, social support, immigration challenges, and alienation were independent predictors of depressed mood. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Many explanatory models of immigrant women’s depression also include social support (Ayers et al, 2009; Dunn & O’Brian, 2009; Levitt, Lane, & Levitt, 2005; Miller, Sorokin, & Fogg, 2013; Remmenick, 2005). Social support includes material as well as emotional support and has two dimensions – perceived and actual/enacted support.…”
Section: Explanatory Models Of Depression In Immigrant Womenmentioning
confidence: 99%
“…Many explanatory models of immigrant women’s depression also include social support (Ayers et al, 2009; Dunn & O’Brian, 2009; Levitt, Lane, & Levitt, 2005; Miller, Sorokin, & Fogg, 2013; Remmenick, 2005). Social support includes material as well as emotional support and has two dimensions – perceived and actual/enacted support.…”
Section: Explanatory Models Of Depression In Immigrant Womenmentioning
confidence: 99%
“…More specifically, studies that have examined groups by country or special group of population suggested that the association is not universal across immigrant ethnicity and sub-groups. For example, the pattern that nativity and other social contributors associated with depressive symptoms among women was different from that among men (22,23), moreover, women were reported to be more vulnerable to depressive symptoms in the context of chronic conditions (24) and gender may have interaction with other risk factors (25); first generation immigrants were more likely to have mental health symptoms with the increasing of acculturative stress compare to second and third generations (22), however previous literature does not provide an in-depth understanding of depression etiologies among first-generation immigrants. Furthermore, studies also found that Asian immigrants are not a homogenous group in the context of differences of depression experienced.…”
Section: Introductionmentioning
confidence: 99%
“…Immigrants, in particular, can face a multitude of challenges when entering a host country (e.g. language barriers 4,5 , separation from family, feelings of loss 4,6 , alienation 7 , perceived discrimination 4,8 ). The number of residents in the United States today who are foreign-born is at a record high, representing a 313% increase compared to 50 years ago (slightly fewer than 10 million in 1960 versus approximately 40 million in 2010 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety, depression, distress, and feelings of loss are common factors noted in individuals who are not assimilated or integrated to their host country 6,7,13,14 . For example, the Travellers, a historically nomadic cultural group of people residing in Ireland, maintain a strong sense of ethnic identity; their separation from the surrounding dominant Irish culture is considered a primary reason for the increased risk of substance abuse among this group 15 .…”
Section: Introductionmentioning
confidence: 99%